Clinical and pathologic features of Crimean-Congo hemorrhagic fever - (:unkn) unknown (Springer Netherlands, 2007)
This chapter describes the story of the clinical process starting from the entrance of the virus to the human body to the death, if happens. Humans are the only known host of Crimean-Congo hemorrhagic fever virus (CCHFV) in which disease is manifested [18]. In general, the people living in endemic areas are at risk. But some of the people have higher risk, which were described in Section V. Among the people, who are at risk, some can get the infection, and then some get the disease (Box 16-1). In a Russian study, the probability of getting the disease for subjects who had been infected was found to be 0.215; in other words, the estimated ratio of apparent to inapparent infections suggests that one of every five persons infected develops Crimean-Congo hemorrhagic fever (CCHF) [15]. This rate was reported to be much higher than other diseases such as western equine encephalitis, St. Louis encephalitis, and tick-borne encephalitis [15]. In another study from Turkey, these rates were found to be similar [14]. In that study, the infection rate was 15/55 (27%) in the endemic region, and the attack rate was 11/55 (20%). The infection rate was significantly higher 8/19 (42%) among the individuals, who had the history of tick bite [14]. The gender and the age distribution among the cases are closely related to the exposure risk to the ticks in endemic regions. Accordingly, the rate of the diseased female is 25% in Iran [1], whereas 50% in Turkey [11]. © 2007 Springer Netherlands. All rights reserved.